1990
DOI: 10.1210/endo-126-6-3200
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids: Potent Inhibitors and Stimulators of Growth Hormone Secretion*

Abstract: Excessive glucocorticoid concentrations are well recognized inhibitors of linear growth, due in part to their suppression of GH secretion. The mechanism of this inhibition has been unclear, especially since glucocorticoids enhance the in vitro GH response of pituitary cells to GH-releasing hormone (GHRH). We investigated the possibility that hypothalamic somatostatin might be mediating these dichotomous observations by using passive immunization techniques. The GH response to GHRH was significantly blunted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(83 citation statements)
references
References 27 publications
4
76
0
3
Order By: Relevance
“…In rats, spontaneous GH levels were significantly decreased and the GH-releasing hormoneinduced GH response was blunted after 4 d of DEXA treatment. Subsequent immunologic neutralization of somatostatin, however, resulted in a significantly enhanced GH response, suggesting that steroids inhibit the GH response to GHreleasing hormone by increasing the hypothalamic somatostatin secretion (27). Miell et al (34), however, found in healthy volunteers a persistent but attenuating rise in serum GH levels after 4 d of DEXA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rats, spontaneous GH levels were significantly decreased and the GH-releasing hormoneinduced GH response was blunted after 4 d of DEXA treatment. Subsequent immunologic neutralization of somatostatin, however, resulted in a significantly enhanced GH response, suggesting that steroids inhibit the GH response to GHreleasing hormone by increasing the hypothalamic somatostatin secretion (27). Miell et al (34), however, found in healthy volunteers a persistent but attenuating rise in serum GH levels after 4 d of DEXA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Inasmuch as we present the first data of an acute DEXA effect on serum GH levels in preterm infants, we cannot compare our results with other studies in preterm infants. In older individuals the effects of glucocorticoids on spontaneous and stimulated GH secretion appear contradictory (25)(26)(27). Chronic hypercortisolism inhibits spontaneous and stimulated GH secretion in children and adults (9 -11, 28).…”
Section: Discussionmentioning
confidence: 99%
“…hexarelin remain responsive to subsequent GHRH stimulation (L K Conley, R C Gaillard, A Giustina, R S Brogan & W B Wehrenberg, unpublished observations) and others have reported a maintained responsiveness to GHRH or the opiate agonist MRZ 2549 during continuous GHRP-6 exposure (Sartor et al 1985b, Clark et al 1989. In addition, although others have reported increases in cortisol in response to intermittent GHRP-6 treatment in man (Hayashi et al 1991, Frieboes et al 1995, Thomas et al 1997), a sustained increase in this inhibitor of GH secretion (Wehrenberg et al 1990) is an unlikely explanation, as we found that corticosterone concentrations were not significantly elevated in response to long-term exposure to hexarelin (Fig. 4A).…”
Section: Figure 3 (A)mentioning
confidence: 98%
“…Many lines of evidence suggest that hypothalamic somatostatin (SRIF) is chiefly responsible for GC-induced CH suppression [11][12][13].…”
mentioning
confidence: 99%